Minimum Maximum Stock Level (MMSL) Analysis for Pareto A Cardiovascular Medicines: Evidence from a Community Pharmacy in Bandung, Indonesia - Ramadhan, Iqbal Sujida; Kautsar, Angga Prawira (Universitas Muhammadiyah Yogyakarta, 2026)
The availability of cardiovascular medications is a crucial component of pharmaceutical services in community pharmacies, as it directly affects the continuity of patient therapy. Various studies have discussed drug inventory control, but research evaluating the performance of high-value (Pareto A) cardiovascular drug inventory management using a stockout-episode-based approach in community pharmacies remains limited, particularly in the context of implementing the Minimum Maximum Stock Level (MMSL) method. This study aims to analyze the impact of implementing MMSL on the performance of pareto A cardiovascular drug inventory management in community pharmacy in Bandung, Indonesia. This study uses a quasi-experimental nonequivalent control-group design to compare stockout indicators before and after the implementation of MMSL. The research subjects were selected purposively. The analysis of stockout episodes was conducted using Poisson Regression. In contrast, the duration of stockouts and the value of stockout losses per episode were analyzed using the Mann-Whitney U test. The results showed that implementing MMSL led to a non-significant decrease in stockout episodes (from 1.50 to 1.33 per month; p = 0.782; IRR = 1.125). The duration of stockouts showed a non-significant increase (from 3.0 days to 4.0 days, p = 0.284, r = 0.21). However, the value of stockout losses per episode increased significantly (from IDR 314,223 to IDR 744,746, p = 0.048, r = 0.39). The conclusion of this study indicates that MMSL plays a role in preventing stockouts, but risk management for high-value items still requires additional strategies in pharmaceutical inventory management.